Open Tourism Open Innovation, Crowdsourcing and Co-Creation Challenging the Tourism Industry - Egger, Roman; Gula, Igor.; Walcher, Dominik; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2016)
Open Innovation, Crowdsourcing and Co-creation have recently gained considerable attention among academics, as well as in practice, and have become intensively researched and discussed topics. Their use has already been discussed in various fields, and the body of literature on them is growing steadily. In light of the diversity of the projects and initiatives from all over the world, these phenomena would appear to have already found their way into various areas of industry and society. The tourism industry is one of the biggest industries and its markets are largely saturated, with constantly falling profit margins on the one hand, and with rapidly changing customer needs and demands on the other. The need for change, renewal and differentiation is based on a complex combination of forces; therefore the ability to innovate has become an essential factor in companies$1 (Bcontinuing existence. Especially the development of the internet and its revolutionary impact on the product and process level of companies has sparked an increase in innovation literature concerning tourism. However, it seems even more surprising that to date, little or no attention has been given to the paradigm shift in innovation management from (3z(Bclosed(3y (Bto open innovation forced by the internet, and above all by Social Media. The book examines the concepts of Open Innovation, Crowdsourcing and Co-creation from a holistic point of view and analyzes their suitability for the tourism industry. Methods, theories and models are discussed and examined regarding their practical applicability. The book addresses the needs of academics and practitioners in the tourism industry alike, as well as managers throughout the tourism industry, introducing them to the theoretical mechanisms and principles of Open Innovation, Crowdsourcing and Co-creation with case studies and best practice examples.s
Part A: Theoretical Fundamentals and Concepts -- Part B: Case Studies - Information Level -- Part C: Case Studies - Creation Level -- Part D: Case Studies - Provision Level -- Part E: Further Open Tourism Examples and Cases.
Keywords: Business; Marketing; Management; Industrial management; Information technology; Business -- Data processing; Business and Management; Innovation/Technology Management; IT in Business; Marketing; Electronic books